Evolutionary and functional impact of common polymorphic inversions in the human genome - Carla Giner-Delgado (Nature Portfolio, 2019)
Inversions are a little-studied type of genomic variation that could contribute to phenotypic traits. Here the authors characterize 45 common polymorphic inversions in human populations and investigate their evolutionary and functional impact.